Metabolomics analysis of antiquitin deficiency in cultured human cells and plasma: Relevance to pyridoxine‐dependent epilepsy. Issue 1 (27th October 2022) - Crowther, Lisa M.; Poms, Martin; Zandl‐Lang, Martina; Abela, Lucia; Hartmann, Hans; Seiler, Michelle; Mathis, Déborah; Plecko, Barbara
Abstract: Deficiency of antiquitin (α‐aminoadipic semialdehyde dehydrogenase), an enzyme involved in lysine degradation and encoded by ALDH7A1, is the major cause of vitamin B6 ‐dependent epilepsy (PDE‐ALDH7A1). Despite seizure control with high dose pyridoxine (PN), developmental delay still occurs in approximately 70% of patients. We aimed to investigate metabolic perturbations due to possible previously unidentified roles of antiquitin, which may contribute to developmental delay, as well as metabolic effects of high dose pyridoxine supplementation reflecting the high doses used for seizure control in patients with PDE‐ALDH7A1. Untargeted metabolomics by high resolution mass spectrometry (HRMS) was used to analyze plasma of patients with PDE‐ALDH7A1 and two independently generated lines of cultured ReNcell CX human neuronal progenitor cells (NPCs) with CRISPR/Cas mediated antiquitin deficiency. Accumulation of lysine pathway metabolites in antiquitin‐deficient NPCs and western‐blot analysis confirmed knockdown of ALDH7A1 . Metabolomics analysis of antiquitin‐deficient NPCs in conditions of lysine restriction and PN supplementation identified changes in metabolites related to the transmethylation and transsulfuration pathways and osmolytes, indicating a possible unrecognized role of antiquitin outside the lysine degradation pathway. Analysis of plasma samples of PN treated patients with PDE‐ALDH7A1 and antiquitin‐deficient NPCs cultured in conditions comparable to the patient plasma samples demonstrated perturbation of metabolites of the gamma‐glutamyl cycle, suggesting potential oxidative stress‐related effects in PN‐treated patients with PDE‐ALDH7A1. We postulate that a model of human NPCs with CRISPR/Cas mediated antiquitin deficiency is well suited to characterize previously unreported roles of antiquitin, relevant to this most prevalent form of pyridoxine‐dependent epilepsy.